Human Resource Planning: Then and Now - Mallela, Chandrasekhar Sita Rama (Prabandhan: Indian Journal of Management, 2012)
Human Resources Planning determines the human resources required by the organization to achieve its strategic goals. The process of Human Resource Planning consists of primarily business strategic plans, resource strategy, scenario planning, demand and supply forecasting, labor turnover analysis, work environment analysis and operational effectiveness analysis. This article dwells on the differences between the older practices and the current practices of a HR Manager in the above chief constituents of the human resources planning.